Comparative Biological Pathotyping of Newcastle Disease Virus Sub-genotypes VIIg, VIIh, and VIIi in Specific Pathogen Free (SPF) Chickens - Y. M. Utami; S. Widyarini; M. H. Wibowo (Faculty of Animal Science, Bogor Agricultural University, 2023)
Newcastle Disease (ND) is an infectious viral disease in poultry caused by the Newcastle Disease virus (NDV). The NDV that causes ND cases in Indonesia is genotype VII with various sub-genotypes. This study was conducted to compare the in vivo pathogenicity of ND virus sub-genotypes VIIg, VIIh, and VIIi in specific pathogen free (SPF) chickens. The virus isolates were isolated and identified as ND virus sub-genotypes VIIg, VIIh, and VIIi. The level of pathogenicity is known by calculating the mean death time (MDT) and the intravenous pathogenicity index (IVPI). The comparations of lesions of NDV were analyzed descriptively and statistically based on clinical signs, the ratio of lymphoid organ weight, and lesions in hematoxylin-eosin (HE). Isolate confirmation was conducted by harvesting the lung organs. ND was detected using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) using specific primers of the fusion (F) fragment gene. The sequence was compared with that of other NDVs from GenBank and Analyzed using MEGA-6 software. The analysis results showed that the VIIh and VIIi sub-genotypes were virulent strains due to the MDT <60 hours with IVPI value index of 3.0, the lymphoid organs showing atrophy and lymphocyte depletion. On the other hand, the VIIg sub-genotype was a less virulent strain because it had an IVPI index of 0.0 with MDT >60 hours, and the lymphoid organs showed mild lymphocyte depletion. Based on the in vivo results with the sequence analysis at the cleavage site showed that ND isolates Sub-genotypes VIIh (112RRQRRF117) and GVIIi (112RRQKRF117) were virulent strains, but Sub-genotype VIIg (112GRQGRL117) was less virulent.